Aposições restritivas oracionais em textos escritos do português contemporâneo - Sales, Rayssa Barroso (2024)
This paper delves into the study of restrictive appositional clauses in contemporary Brazilian Portuguese written texts. Restrictive appositional clauses are understood as constructions where a clause explicitly specifies the content generically encapsulated by a noun and connects to it via a preposition (Nogueira, 2017, p. 6). Quirk et al. (1985), Matthews (1981), and Meyer (1989) discuss these appositions in examples such as those starting with “the fact that...,” termed that-apposition. Nogueira (2017) identifies these constructions in Portuguese, also analyzed as restrictive appositions, as in “O fato de que ele está partindo” (Matthews, 1981, p. 231). Specific objectives include: i) identifying the type of subact the restrictive appositional clause performs; ii) verifying the categories represented by the noun that encapsulates and projects the appositional clause's content; iii) identifying nouns (type and token) that function as the apposition's nucleus and analyzing how they relate to the content instantiated by the structure; iv) checking if there are nominal elements with relational nature or transitive cognate verbs in restrictive appositional clauses; v) analyzing the element linking the encapsulating noun to the encapsulated content in appositional clauses; vi) investigating the textual-discursive functions of these restrictive appositional constructions concerning textual and argumentative strategies; vii) identifying the morphosyntactic structure characterizing the restrictive appositional clause. The theoretical foundation is based on the Functional Discourse Grammar (Hengeveld; Mackenzie, 2008), which considers the Discursive Act as the unit of analysis, adequately allowing the analysis of such appositions. The occurrences for analysis were obtained from the same corpus used by Nogueira (1999) from the database at the Lexicographic Studies Center of the Faculdade de Ciências e Letras, UNESP Campus, Araraquara-SP, consisting of 36 written texts, with 12 from the oratory genre, 12 from the dramatic genre, and 12 from the technical genre. Additionally, samples of journalistic texts such as opinion articles, editorials, news, and reports organized by Nogueira (2002) were used. Data analysis indicates that restrictive appositional clauses have generic nouns (e.g., fact, idea) as nuclei, connected to a clause via a preposition, establishing an equivalence relationship with a textual-discursive projection strategy, enabling textual strategies linked to nominalization. At the Interpersonal Level, results show that the restrictive appositional clause occurs as a Referential Subact; at the Representational Level, results indicate that the categories represented by the noun in restrictive appositional clauses are State-of-affairs, Propositional Content, and Communicated Content.